Rear Wheel Independent Drive Electric Vehicle Yaw Stability Control System Design and Analysis - Koc, Celal Tayfur; Emirler, Mumin Tolga (IEEE, 2022)
This paper introduces rear wheel traction based fully electrical vehicle lateral stability controller design with independently driven electric motors. The proposed controller consists of two stages: lower and upper controllers. The upper controller is the proportional-integral (PI) controller, which calculates the required corrective yaw moment based on the desired and actual yaw rate of the vehicle. The proposed PI controller design method relies on the parameter space approach (PSA) considering D-stability. The time domain and frequency domain requirements are visualized by contour plotting method on the proportional-integral gain parameter plane. This multi-objective visualization assists designers while selecting an appropriate PI controller gain pairs. The lower controller distributes tire forces based on the vehicle's actual and desired situation using a torque distribution algorithm. The double-track vehicle model is employed to validate the proposed control system under different driving scenarios in MATLAB/Simulink. The results show that by using only the traction forces generated independently on the rear wheels, the lateral control of the vehicle considering D-stability, settling time, overshoot, bandwidth, rise time, integral-time-absolute-error and phase margin criteria could be accurately achieved under beforehand defined driving conditions.
Keywords: electric vehicle; control systems; yaw stability control; parameter space; D-stability; Computer Science; Engineering